` PENGARUH LKPD BERBASIS PERMAINAN TRADISIONAL BANTEN UNTUK MENDUKUNG KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Rohadatul Aisy, Salma; Khaerunnisa, Etika (Nabla Dewantara: Jurnal Pendidikan Matematika, 2024)
Problem-solving skills are essential mathematical abilities that students must possess. However, students' mathematical problem-solving skills remain low, often due to ineffective teaching methods and monotonous instructional materials that fail to meet the characteristics and needs of student learning. This study aims to examine the impact of student worksheets (LKPD) based on traditional games from Banten on supporting students' mathematical problem-solving abilities. The method used is a Systematic Literature Review (SLR) involving the collection, evaluation, and analysis of data from 15 scientific articles related to the topic. The results show that the use of LKPD in various approaches, such as Problem Based Learning (PBL) and ethnomathematics, is effective in enhancing students' problem-solving skills. Additionally, traditional Banten games such as engklek, gatrik, egrang batok, congklak, and gobak sodor have been proven to significantly support mathematical problem-solving abilities. Therefore, the use of LKPD based on traditional games can create more interactive and enjoyable learning, positively impacting the improvement of students' mathematical problem-solving skills.